Left Atrial Appendage Pseudothrombus Is Associated With Stroke History in Patients With Atrial Fibrillation Undergoing Cardiac Computed Tomography - Edward Nicol; Nabeela Karim; Tom Semple; Saranya Baleswaran; Ruth Owen; Omar Riad; Vias Markides; Simon P. G. Padley; Tom Wong (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background In nonvalvular atrial fibrillation (NVAF), the left atrial appendage (LAA) is the source of thrombus in up to 90% of patients. LAA pseudothrombus (LAAPT), defined as a filling defect on the initial but not the 60‐second delayed acquisition on cardiovascular computed tomography scan (CCT), is a recognized phenomenon in NVAF, with unknown clinical relevance. We aimed to determine the relationship between LAAPT and history of stroke in patients with NVAF. Methods and Results The study included 213 consecutive patients with NVAF undergoing CCT who were assessed for LAAPT. LA and LAA dimensions and LAA morphology correlated with clinical demographics including cardiovascular risk factors, history of stroke, thromboembolic stroke, and transient ischemic attack. Mean age (±SD) was 65.1±10.5 years (range 31–89) and 150 of 213 (70.4%) were men. LAAPT was present in 59 of 213 (27.7%) patients. Greater mean LAA ostium area (5.7 versus 4.5, P<0.001), greater mean LAA ostium area:curved length (0.11 versus 0.08, P<0.001), increased LAA volume (14.0 versus 10.2, P<0.001), and lower mean LAA tortuosity index (1.17 versus 1.38, P<0.001) were all associated with the presence of LAAPT. On multivariable analysis, LAAPT on CCT (odds ratio [OR], 3.20 [95% CI, 1.40–7.20]; P<0.006) and higher CHA2DS2‐VASc score (OR, 1.65 [95% CI, 1.16–2.35]; P=0.01) were associated with all strokes, with LAAPT remaining a statistically significant risk factor even after adjustment for CHA2DS2‐VASc score. Conclusions LAAPT on CCT is common in patients with NVAF. It has a strong positive association with stroke prevalence, even after adjustment for CHA2DS2‐VASc score. LAAPT on CCT may potentially allow further stratification for stroke risk, additive to the CHA2DS2‐VASc score.